Urinary Cell-Free DNA Quantification as Non-Invasive Biomarker in Patients with Bladder Cancer - Brisuda, Antonin; Pazourkova, Eva; Soukup, Viktor; Horinek, Ales; Hrbáček, Jan; Capoun, Otakar; Svobodova, Iveta; Pospisilova, Sarka; Korabecna, Marie; Mares, Jaroslav; Hanuš, Tomáš; Babjuk, Marek (Urologia internationalis, 2016)
INTRODUCTION: Concentration of urinary cell-free DNA (ucfDNA) belongs to potential bladder cancer markers, but the reported results are inconsistent due to the use of various non-standardised methodologies. The aim of the study was to standardise the methodology for ucfDNA quantification as a potential non-invasive tumour biomarker. MATERIAL AND METHODS: In total, 66 patients and 34 controls were enrolled into the study. Volumes of each urine portion (V) were recorded and ucfDNA concentrations (c) were measured using real-time PCR. Total amounts (TA) of ucfDNA were calculated and compared between patients and controls. Diagnostic accuracy of the TA of ucfDNA was determined. RESULTS: The calculation of TA of ucfDNA in the second urine portion was the most appropriate approach to ucfDNA quantification, as there was logarithmic dependence between the volume and the concentration of a urine portion (p = 0.0001). Using this methodology, we were able to discriminate between bladder cancer patients and subjects without bladder tumours (p = 0.0002) with area under the ROC curve of 0.725. Positive and negative predictive value of the test was 90 and 45%, respectively. CONCLUSION: Quantification of ucf DNA according to our modified method could provide a potential non-invasive biomarker for diagnosis of patients with bladder cancer.
Keywords: Real-Time Polymerase Chain Reaction; Female; Cell-Free System; ženské pohlaví; bezbuněčný systém; Predictive Value of Tests; Reproducibility of Results; prediktivní hodnota testů; Urinalysis; DNA; lidé; Sensitivity and Specificity; studie případů a kontrol; senzitivita a specificita; ROC křivka; reprodukovatelnost výsledků; Male; Urinary Bladder Neoplasms; nádorové biomarkery; Aged; Case-Control Studies; nádory močového měchýře; analýza moči; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; Middle Aged; kvantitativní polymerázová řetězová reakce; ROC Curve; Humans